LINGUOCULTURE OF COLOR IN RUSSIAN AND UZBEK PHRASEOLOGISTS (Web of Teachers: Inderscience Research, 2024)
Linguocultural information is knowledge of the entire system of cultural values expressed in language, wrote V.V. Vorobyov. It is believed that every nation has so-called key words, which are often used in proverbs and sayings, reflecting color interpretations of traditions and the spirit of the people. Phraseologisms are carriers of a special cultural and value code for the entire linguistic society.